EVALUASI IMPLEMENTASI KEPUTUSAN GUBERNUR BALI TENTANG REALOKASI HASIL PENERIMAN PHPR KABUPATEN BADUNG DAN KOTA DENPASAR KEPADA PROVINSI BALI (STUDI KASUS KABUPATEN TABANAN - FADHILA, EKA (CITIZEN CHARTER, 2014)
Purpose of this research is to evaluate implementation Decision of Governor Bali. This research use descriptive method qualitative. As for its data collecting method is interview, observation, and documentation study. Pursuant to result of research from 13 indicator variable efficacy of policy implementation according to Grindle there are 5 indicator variable having problem is. First, content order policy, which is on its implementation contain difference of perception among relevant implementator of content order this policy. Second, existence of sanction, where it is true there no coherent sanction in this policy. Third, clarity of message of policy, message of this ill defined policy causing multiple of interpretation among implementator which is on finally cause at difference of relevant perception of usage of this fund. Fourth, policy consistency where this policy represent to continues of previous policy, and there is lessened in the case of aspect and consistency ofÂ  acountability because on the happening of change at this policy do not entangle stakeholder which in this case is party receiver of fund of realocation. Fifth, acceptance of message which not yet taken place in an optimal fashion because there is still its of difference of perception among implementator so that policy implementation not yet earned to walk optimally.